A practical management of children with antibiotic allergy - Calamelli, Elisabetta; Caffarelli, Carlo; Franceschini, Fabrizio; Saretta, Francesca; Cardinale, Fabio; Bernardini, Roberto; Liotti, Lucia; Mori, Francesca; Crisafulli, Giuseppe; Caimmi, Silvia; Bottau, Paolo (Acta Biomedica Atenei Parmensis, 2019)
About 10% of the parents reported that their children are allergic to one drug and the betalactam antibiotics are the most frequently suspected. Even if most of the adverse events following antibiotic prescriptions to children are considered allergic, after a full allergy work-up only a few of the suspected reactions are confirmed. For this reason, many children are incorrectly labelled as “allergic” and this represents an important challenge for the choice of the antibiotic therapy in these “labelled” children, who are frequently improperly deprived of narrow-spectrum antibiotics because considered as allergic. When an allergic reaction is suspected a precise diagnosis and a choice of a safe and effective alternative is essential for the future antibiotic option. In the light of this, the main aim of this paper is to try to provide a practical approach to managing the individuals who have reported adverse reactions to antibiotics.